A randomized Phase III trial of lobe-specific vs. systematic nodal dissection for clinical Stage I–II non-small cell lung cancer (JCOG1413). (21st November 2017) - Hishida, Tomoyuki; Saji, Hisashi; Watanabe, Shun-ichi; Asamura, Hisao; Aokage, Keiju; Mizutani, Tomonori; Wakabayashi, Masashi; Shibata, Taro; Okada, Morihito; ,
Abstract : A randomized Phase III trial was commenced to confirm the clinical benefit of lobe-specific nodal dissection in comparison to systematic nodal dissection for clinical Stage I–II non-small cell lung cancer. Abstract: In January 2017, the Lung Cancer Surgical Study Group of the Japan Clinical Oncology Group commenced a randomized Phase III trial to confirm the clinical benefit of lobe-specific nodal dissection for clinical Stage I–II non-small cell lung cancer. The primary endpoint is overall survival, and the main objective is to confirm the non-inferiority of lobe-specific in comparison to systematic nodal dissection with regard to lobectomy. The secondary endpoints are relapse-free survival, %local recurrence, %regional lymph node recurrence, operation time, blood loss, length of hospitalization, duration of chest tube placement and adverse events. A total of 1700 patients will be accrued from 44 Japanese institutions within 5 years. This study is the first and large prospective trial to evaluate whether the difference in the area of nodal dissection affects the overall survival of patients with relatively early-stage non-small cell lung cancer. This trial has been registered in the UMIN Clinical Trials Registry as UMIN000025530.